Cytological study of palpable breast lumps presenting in an Indian rural setup - Smita Balwantrao Sankaye; Suyrakant Dattatreya Dongre (Indian Journal of Medical and Paediatric Oncology)
Introduction: Benign as well as malignant breast lesions are quite common in Indian population. It is the second most common cancer site after cancer cervix. Fine-needle aspiration cytology (FNAC) is safe, reliable, and time saving outdoor procedure with little discomfort to the patient. FNAC is useful in diagnosis and further planning of treatment without need for biopsy. The current study was carried out with aims of studying the frequency of various breast lesions on FNAC in a rural area in India and its histopathological correlation. Materials and Methods: This was 2 years prospective study carried out from May 2010 to April 2012. Physical examination of breast mass by palpation was done. Smears were stained with May-Grunwald Giemsa and Papanicolaou stain. Results: Of the 225 cases, 131 were in the benign category and 65 belonged to the malignant category, while the cytology study of 13 cases was unsatisfactory. Seventy-six cases were available for histological correlation. Of 29 cytological benign cases, 26 were confirmed as benign, but 3 turned out to be malignant. Out of 36 cytological malignant cases, 35 were confirmed as malignant. FNAC was 88.37% sensitive and 96.42% specific in diagnosing malignant lesions. Conclusion: Fine-needle aspiration cytology is a rapid and effective method for the primary categorization of palpable breast lumps into benign, malignant, atypical, suspicious, and unsatisfactory categories. Benign breast lesions are common than malignant lesions. Histological correlation indicated FNAC to be a good diagnostic tool.